2019
DOI: 10.1016/j.palaeo.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and extirpation selectivity patterns of brachiopods and bivalves across a Carboniferous glacial to non-glacial transition (Pennsylvanian, central western Argentina) and their influence in building the biotic bathymetric gradient

Abstract: Please cite this article as: D. Balseiro, K. Halpern , Immigration and extirpation selectivity patterns of brachiopods and bivalves across a Carboniferous glacial to non-glacial transition (Pennsylvanian, central western Argentina) and their influence in building the biotic bathymetric gradient. Palaeo (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…However, this may not be the entire explanation, as some other groups also show elevated rates of speciation and extinction during this time interval. For instance, Balseiro (2016) and Balseiro & Halpern (2019) did document evolutionary turnover at high latitudes, and elevated evolutionary rates have also been found in fusulinid foraminifera (Groves & Lee, 2008; Groves & Yue, 2009) and advanced cladid crinoids (Segessenman & Kammer, 2018). Ultimately, we support the contention raised by Segessenman & Kammer (2018) that patterns from a few individual groups do not refute the general pattern of sluggish macroevolution postulated for this time period in the history of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this may not be the entire explanation, as some other groups also show elevated rates of speciation and extinction during this time interval. For instance, Balseiro (2016) and Balseiro & Halpern (2019) did document evolutionary turnover at high latitudes, and elevated evolutionary rates have also been found in fusulinid foraminifera (Groves & Lee, 2008; Groves & Yue, 2009) and advanced cladid crinoids (Segessenman & Kammer, 2018). Ultimately, we support the contention raised by Segessenman & Kammer (2018) that patterns from a few individual groups do not refute the general pattern of sluggish macroevolution postulated for this time period in the history of life.…”
Section: Discussionmentioning
confidence: 99%
“…(Previous studies of ammonoids have shown that these changes in sea-level may have caused more significant changes in biogeographic ranges of taxa than temperature changes during this time period, and other time periods as well (Hallam, 1987; Hartenfels & Becker, 2016; Zhang et al, in press). Those changes impacted patterns of geographic range in both terrestrial plant (e.g., DiMichele et al, 2009; Falcon-Lang & DiMichele, 2010) and marine invertebrate ecosystems (e.g., Ramsbottom, 1981; Leighton, 2005; Powell, 2007; Waterhouse & Shi, 2010; Balseiro & Halpern, 2019). When it comes to marine invertebrates from this time interval, most of the focus has been on the highly diverse benthic faunas (e.g., Stanley & Powell, 2003; Powell, 2007; Bonelli & Patzkowsky, 2011; Balseiro, 2016; Segessenman & Kammer, 2018; Balseiro & Halpern, 2019); however, taxa that have a pelagic life style are also worth examining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latitudinal range (maximum observed paleolatitude minus minimum observed paleolatitude) is also used commonly to characterize geographic range sizes (Powell 2005, 2007; Foote and Miller 2013; Finnegan et al 2016; Balseiro and Halpern 2019; Darroch et al 2020). Unlike a convex hull, latitudinal range is a linear metric and may reflect breadth of thermal tolerance (Jackson 1974; Stanley and Powell 2003; Powell 2007; Sunday et al 2012), with larger latitudinal ranges potentially indicating greater thermal tolerances.…”
Section: Methodsmentioning
confidence: 99%
“…The late Paleozoic is interesting from a macroevolutionary perspective, because it was a time of “sluggish” evolution when global rates of origination and extinction were low (Stanley and Powell 2003; Powell 2005; Segessenman and Kammer 2018; Balseiro and Halpern 2019; Kolis and Lieberman 2019) in spite of dramatic, cyclical changes in climate and the environment (Parrish 1993; Olszewski and Patzkowsky 2001a,b; Raymond and Metz 2004; Horton et al 2012; Balseiro 2016). The LPIA was the longest-lasting glacial period of the Phanerozoic, which lasted from 320 to 260 Ma.…”
Section: Introductionmentioning
confidence: 99%